Clinical features and treatment outcomes of liver involvement in paediatric Langerhans cell histiocytosis - Xinshun Ge; Wenxin Ou; Ang Wei; Hongyun Lian; Honghao Ma; Lei Cui; Dong Wang; Liping Zhang; Xiaoman Wang; Lejian He; Rui Zhang; Tianyou Wang (BMC, 2024)
Abstract Langerhans cell histiocytosis (LCH) is the most common histiocytic disorder in children, and liver involvement in LCH is rare. This retrospective study reported the clinical features and prognosis of patients with hepatic LCH. Liver involvement was defined by histopathological findings, liver dysfunction or abnormalities, or ultrasound imaging. A total of 130 patients (14.5%) with hepatic LCH out of 899 in the LCH population were enrolled. Patients with liver involvement had greater frequencies of skin, lung, hearing system, and haematologic system involvement, and hemophagocytic lymphohistiocytosis (P<0.001, 0.001, 0.002, 0.009, and <0.001, respectively). Overall survival and progression-free survival were lower in LCH patients with liver involvement than in those without liver involvement (P<0.001 and <0.001). In patients with liver involvement, the overall survival (OS) and progression-free survival (PFS) rates were lower in patients with cholangitis than in those without cholangitis (P<0.020 and 0.030). For the treatment response, the response rate of hepatic LCH patients to initial first-line therapy (n=89) was 22.5%. However, there was no significant difference in the response rate or recurrence rate between patients who shifted from first-line treatment to second-line treatment (n=29) or to targeted therapy (n=13) (P=0.453 and 1.000). The response rate of hepatic LCH patients who received initial second-line therapy (n=13) was 38.5%. Two of these patients subsequently experienced bone recurrence. The response rate of hepatic LCH patients who received initial targeted therapy (n=16) was 75.0%. Three patients subsequently experienced recurrence, including 2 in the bone and 1 in the liver and skin. A total of 39.3% of patients who received second-line treatment had severe myelosuppression (grade III-IV), and 50.8% had varying degrees of gastrointestinal events, whereas there was no severe toxicity in patients who received first-line treatment and targeted therapy. Four patients underwent liver transplantation because of liver cirrhosis. The patients' liver disease improved within a follow-up period of 18-79 months. This study demonstrated that LCH with liver involvement, especially cholangitis, indicates a poor prognosis. Targeted therapy provides a good treatment response and less toxicity. However, it may relapse after withdrawal. Liver transplantation is still a reliable salvage option for patients with end-stage liver disease.